2012
DOI: 10.1186/1471-2458-12-809
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in disordered eating and weight dissatisfaction in Swiss adults: Which factors matter?

Abstract: BackgroundResearch results from large, national population-based studies investigating gender differences in weight dissatisfaction and disordered eating across the adult life span are still limited. Gender is a significant factor in relation to weight dissatisfaction and disordered eating. However, the reasons for gender differences in these conditions are still poorly understood. The aim of this study was to examine gender differences in weight dissatisfaction and disordered eating in the general Swiss adult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
43
0
19

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(70 citation statements)
references
References 44 publications
(81 reference statements)
8
43
0
19
Order By: Relevance
“…This is in consistent with earlier studies. (20) In line with previous research, (21) more number of women in this study was underweight. However, the number of women those were overweight was higher than men.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…This is in consistent with earlier studies. (20) In line with previous research, (21) more number of women in this study was underweight. However, the number of women those were overweight was higher than men.…”
Section: Discussionsupporting
confidence: 80%
“…These findings differed from previous studies that showed no gender differences in the prevalence of binge eating. (20) On the contrary, nearly half of the men exercised more than sixty minutes and lost weight more than 10kgs in the past six months. Previous studies also found similar findings.…”
Section: Discussionmentioning
confidence: 99%
“…Samkvaemt erlendum rannsóknum eru áhaettuþaettir fyrir faeðuaðhald að vera of þungur og vilja léttast, að vera í megrun og að vera ósáttur við eigin líkamsþyngd. [8][9][10][11] Hérlendis veita rannsóknir á algengi megrunar vísbendingar um faeðuaðhald og hamlandi viðhorf til eigin mataraeðis út frá aldri og kyni. Í nýlegri skýrslu, sem unnin var upp úr könnuninni Heilsa og líðan Ís-lendinga sem var framkvaemd árið 2012, kemur fram að taep 42% kvenna hafi reynt að létta sig og að 8% kvenna 18-44 ára hafi verið með átröskun eða séu að glíma við átröskun.…”
Section: áGripunclassified
“…Þetta eru sömu þaettir og tengjast faeðuaðhaldi í erlendum rannsóknum. [8][9][10][11] Í þessari rannsókn var hamlandi faeðuviðhorf algengast hjá yngsta aldurshópnum sem var 18-29 ára. Líkurnar á að upplifa hamlandi faeðuviðhorf voru haerri hjá þeim sem voru skilgreindir með offitu og meðal þeirra sem voru ósáttir við eigin líkamsþyngd samanborið við þá sem voru í kjörþyngd/undirþyngd og þá sem voru sáttir við eigin líkamsþyngd.…”
Section: Umraeðurunclassified
“…In addition, men usually desire to be more muscular (De Young et al, 2010). Therefore, there are differences in the characteristics of eating behaviors between men and women (Forrester-Knauss & Stutz, 2012).…”
Section: Introductionmentioning
confidence: 99%